Development of Adaptive Artificial Neural Network Security Assessment Schema for Malaysian Power Grids - Al-Masri A.N.; Ab Kadir M.Z.A.; Al-Ogaili A.S.; Hoon Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Backpropagation; Deregulation; Electric load dispatching; Electric load shedding; Electric power system economics; Electric power system security; Electric power transmission networks; Neural networks; Adaptive artificial neural networks; Contingency analysis; Economic considerations; Generation re-dispatch; Power system operators; Remedial actions; Security assessment; Security enhancements; Network security